2009
DOI: 10.4067/s0717-97072009000400012
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Biological Activity of the Essential Oil of Peruvian Lantana Camara

Abstract: The composition of the essential oil from Lantana camara L. (Verbenaceae) obtained by hydrodistillation of the aerial parts was examined by GC, GC/ MS, and 13 C-NMR. The GC analysis showed that carvone is the most abundant monoterpene 75.9%, together with limonene 16.9%, accounting for 92.8% of the oil. The major components were also tested by 13 C-NMR analysis of the essential oil. The L. camara oil was assayed against several microorganisms, showing moderate antibacterial activity against the human pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 13 publications
1
30
2
Order By: Relevance
“…On the other hand our data shows, for the very first time that the farnesene derivatives to be representing more than 20% of the EOLC ( E,E) -farnesene (11.58%), (Z,E)-α-farnesene  5.03%  (E)-β-farnesene (4.04%  (E)-diidro-apofarnesol (1.13%), (Z)-β-farnesene (0.49%), in contrast with other works, which had shown small amounts of these derivates, or only one kind of them in an EOLC (Benites et al, 2009;Padalia et al, 2010). The potential of EOLC against promastigote forms of L. chagasi and L. amazonensis was evaluated in vitro.…”
Section: Resultscontrasting
confidence: 46%
“…On the other hand our data shows, for the very first time that the farnesene derivatives to be representing more than 20% of the EOLC ( E,E) -farnesene (11.58%), (Z,E)-α-farnesene  5.03%  (E)-β-farnesene (4.04%  (E)-diidro-apofarnesol (1.13%), (Z)-β-farnesene (0.49%), in contrast with other works, which had shown small amounts of these derivates, or only one kind of them in an EOLC (Benites et al, 2009;Padalia et al, 2010). The potential of EOLC against promastigote forms of L. chagasi and L. amazonensis was evaluated in vitro.…”
Section: Resultscontrasting
confidence: 46%
“…It was also found that older leaves had less antioxidant activity (55%), indicating loss of secondary metabolites as result of leaf senescence. In another study, L. camara L. essential oil showed high antioxidant activity evaluated by the Trolox equivalent antioxidant capacity assay (TEAC) with a level of 29.0 mmol Trolox/kg (Benites et al, 2009).…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…Oleanonic acid caused a reduction in edema, which validated its in vivo antiinflammatory effect. Another study reported that L. camara essential oil showed a relatively low antiinflammatory activity due to its weak ability to inhibit lipooxygenase (IC50 81.5 mg/mL) (Benites et al, 2009). On the other hand, in vitro assays showed that the alcoholic extract and fucatoside C (121) isolated from L. fucata Lindl.…”
Section: Antiinflammatory Analgesic Sedative and Antipyretic Activitymentioning
confidence: 99%
“…Dalea foliolosa (Aiton) Barrneby (Fabaceae) was collected in Miahuatlán de Porfírio Díaz, Oaxaca, México (16° 34.31' N, 0.96° 58.07' W, 1580masl) during 2014-2016. The identity of the plant was certified at the Herbarium-FCME-UNAM-Mexico where a reference voucher 150042 was deposited.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Currently, little is known about the volatile composition and biological activities of many members of the Dalea genus. Up to now, only the volatile profiles of D. coerulia, D. formosa and D. strobilacea have been formally published (Arango et al, 1994;Lucero et al, 2005;Benites et al, 2016). Dalea foliolosa is an annual plant included in the Electronic Atlas of the Mexican Traditional Medicine because of its anti-inflammatory and hypoglycemic properties (UNAM, 2017).…”
Section: Introductionmentioning
confidence: 99%